A Comparative Study of Cardiac Toxicity Analysis in Hypo-Fractionated Vs Conventionalfractionated Adjuvant Radiotherapy in Post-Mastectomy Leftbreast Carcinoma - Begum, Sonya; Rumman, M Kamruzzaman; Haq, Md Nazmul; Afrin, Tania; Mamun, Al; Hossain, Tasneem; Tania, Kamrun Nahar; Huque, Md Shariful; Islam, Johirul; Akhter, Bipasha; Hossen, Md Moarraf (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Post-mastectomy adjuvant radiotherapy improves long-term survival by reducing the risk of loco-regional recurrence in breast cancer patients with high-risk features. Considering radiation therapy to the left sided chest wall heart is an important organ at risk. Hypo-fractionated radiotherapy is increasingly being used due to involvement of fewer treatment sessions and is almost radio-biologically equivalent to conventionally fractionated radiotherapy. Objective: This study was conducted to evaluate cardiac toxicities between hypo and conventionally fractionated radiotherapy. Methods: This quasi-experimental study was done at the National Institute of Cancer Research and Hospital, Mohakhali, Dhaka from January 2019 to December 2019, 60 patients were purposively assigned into two groups and each group included 30 patients. Arm A: received Conventional fractionated radiotherapy (50Gy/25 fractions over 5 weeks, at 2Gy/fraction). Arm B: received Hypo- fractionated radiotherapy (40.05 Gy in 15 fractions over 3 weeks at 2.67 Gy/fraction). Echocardiography (ECHO), Electrocardiography (ECG) was performed to find the cardiac toxicities. Results: The mean age of the patients in arm A was 50.03 ± 6.82 years and that of arm B was 48.08 ± 5.08 years. No significant statistical difference was found between the two groups regarding socio-demographic variables and clinical presentations. Most of the patients in both arms showed grade 0 cardiac toxicity (arm A: 70% and arm B: 80%) & few showed grade 1 cardiac toxicity (arm A: 20% and arm B: 13.3%) and three patients (10.0%) in arm A and two patients (6.66%) in arm B had shown grade 2 cardiac toxicities six months after treatment. However, this difference was statistically not significant (p >0.05). Before treatment, the ejection fraction (EF) of arm A and arm B were 63.3 ± 5.621 and 64.7± 4.991. Six months after treatment the EF of both arms decreased (arm A 60.2 ± 4.051 & arm B 60.9 ± 5.121) but the difference was statistically not significant (p >0.05). Conclusion: Hypo-fractionated radiotherapy in the adjuvant setting for the treatment of left breast cancer has no additional cardiac toxicity in comparison to conventionally fractionated radiotherapy while maintaining same efficacy. J Bangladesh Coll Phys Surg 2024; 42: 169-175